Effect of massage on mature face skin - Kliukovič, Kotryna; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2021)
The theme of the effect of a cosmetic face massage on mature face skin is of great relevance, especially if one wants to reduce the symptoms caused by the aging process.The aim of the investigation. To determine the effect of a cosmetic massage on mature face skin.Methods. A questionnaire survey in writing was carried out on the Internet website www.apklausk.lt. A total of 200 participants took part in the investigation.Results and conclusions of the investigation. As many as 19 per cent of the respondents indicated that the effect of a massage was short-lived, 24.5 per cent of the respondents had a massage of skin regularly.Conclusions. 1. The majority of the respondents started taking care of their skin at the age of 35 and assess the effect of a massage on mature face skin and the importance of regular massage procedures in the positive. One the third of the respondents, being well aware of the importance of a massage, visit a cosmetologist once per month. One the eight of the respondents agreed that a regular face massage prevented early changes in face skin. One the fifth of the respondents noticed that after the face massage procedures the number of mimic wrinkles, as well as redness, decreased, face skin became fresher and more elastic. 2. Due to a lack of information, one the fifth of the respondents do not know what effect a massage has on mature face skin. One the fourth of the respondents think that the effect of a massage on mature face skin is less profound than it was expected.
Keywords: face massage; effect; changes in skin